Penerapan Strategi Semantic Mapping Berbantuan Media Cerita Bergambar untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris siswa (Penelitian Tindakan Kelas di Kelas V MIN 1 Kota Bandung): (Penelitian Tindakan Kelas di Kelas V MIN 1 Kota Bandung) - HANDAYANI, HANIFAH; Saefuddin, Asis; Widowati, Kawuryansih (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The problem in research was about the mastery of English vocabulary among students. Students had difficulties in writing words, understanding their meanings, and constructing correct sentences. Based on interview results, students often did not understand the material presented due to the use of ineffective teaching strategies and media. This condition led to unsatisfactory learning outcomes, as shown by the summative assessment 56% (18 out of 32 students) did not reach the Minimum Mastery Criterion (KKTP) of 75. The purpose of this study was to examine students’ vocabulary mastery before and after the implementation of the strategy, as well as to observe the process in each cycle. This research was conducted using Classroom Action Research two cycles. Data collection methods included observation, interviews, tests, and documentation. The results showed significant improvement. The average student score increased from 58 in the pre-cycle to 75 in the first cycle, and 87 in the second cycle. The percentage of students achieving classical learning mastery also improved from 47% (15 students) in the pre-cycle, to 66% (21 students) in the first cycle, and 88% (28 students) in the second cycle. These results indicate that the applied strategy was effective in improving students’ vocabulary mastery.